Implementing Genre-Based Writing in English Language Teaching Strategies, Challenges, and Solutions - Nur Istiqamah (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2024)
Writing is considered the most complex skill in English language learning as it requires learners to generate, organize, and articulate ideas into coherent texts. This study aims to examine the implementation of the Genre-Based Writing Approach (GBWA) in English language teaching by identifying strategies, challenges, and possible solutions. A qualitative descriptive design was employed using classroom observations, semi-structured interviews, and document analysis of students’ writing. Data were analyzed thematically to capture recurring patterns in instructional practices, difficulties encountered by teachers and learners, and potential solutions for improvement. The findings indicate that strategies such as scaffolding, the use of model texts, collaborative learning, and digital resources significantly enhance students’ writing competence, although teacher expertise, student resistance, and institutional constraints remain major obstacles. The results highlight the importance of teacher training, curriculum reform, assessment alignment, and institutional support for effective implementation of GBWA. The implications of this research provide practical insights for teachers, curriculum designers, and policymakers in enhancing genre-based writing instruction in EFL contexts